Reexamining the associations among community attachment, community-oriented actions, and individual-level constraints to involvement. Issue 1 (1st January 2018) - Theodori, Gene L.
Abstract: Building upon previous research, this study reexamines the associations among community attachment, community-directed behaviors, and individual-level constraints to involvement in community-oriented actions. Using data collected in a general population survey from a random sample of individuals living in 22 rural places in Texas, the following two hypotheses were tested: (1) that community attachment is positively associated with community-oriented actions, and (2) that community attachment is associated with individual-level constraints to involvement in community-oriented actions. The first hypothesis received substantial support; the second hypothesis received moderate support. Possible implications of the findings for researchers, public leaders, Cooperative Extension personnel, and community development practitioners working in local communities in/around rural places containing population settlements are advanced.